PENGELOLAAN MODAL USAHA UNTUK UMKM GADING BERSINAR DEPOK - Risthi, Alyssa; Fitriyah, Fitriyah; Silviyani, Yuli Anita (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Business capital management is one of the main factors that affect productivity in obtaining planned results or outputs. Every MSME must develop its competitive advantage to survive and advance its MSMEs. The level of effectiveness of the use of business capital is very important for the growth and sustainability of MSMEs. If MSMEs lack business capital to expand sales and increase production, they are likely to lose revenue and profits. The size of a capital depends on the type of business it is running, and generally the community recognizes the types of micro, small, medium and large businesses, where each of these types of businesses requires different capital and within certain limits. Every MSME has a main objective, namely MSMEs have the aim of obtaining maximum profit. Therefore, business capital must be managed as effectively as possible so that the profitability of MSMEs can be increased. This PKM activity was carried out for Gading Bersinar Depok MSME players. The existence of this PKM activity is expected that MSME players can find out the development of their business and can manage business capital to support the progress of MSMEs in Gading Bersinar Depok